Analisis Bahasa Gaul Pada Novel Kambing Jantan Karya Raditya Dhika - Prasetiaji, Dwi; , Prof. Dr. Abdul Ngalim, M.M, M.Hum; , Drs. Atiqa Sabardila, M. Hum (2015)
The purpose of this research is 1) to descritif the pattern of communications, 2) to descritif the use of slang on, 3) to descritif know formation of a word on the books, 3) to descritif used sentence that therein appear variety of slang, and 4) to know the implementation in learning the indonesian language . Research is done using a qualitative. The study is done to conduct an observation to the court directly with technical data by observation and recording the context of a conversation, spoken record, and interviews. After the data collected, transkripting data and classified data on domainnya.The result of this research is that using slang for a he-goat the raditya dika more a language used in conversation between the characters in a novel. Conversation / a communication that sanctions could official nature or informal good bersifal flesibel or stiff, the formation of a word used is a actual and it was a common used in intercourse good in indonesian language atapun a foreign language but by doing the change in the word to appear another new vocabulary word, mode of used in book male goat this is what there are variety of the use of the slang is a mode of a sentence as put forward by verhaar and the implementation of a novel kj in learning the indonesian language can be used in basic competence 4.1 writing a diary or a personal experience with expressions and a language that is good and right.